(untitled) (Orthodontic Journal of Nepal, 2022)
Introduction: The choice of orthodontic appliance depends upon the patients age, profession and availability of them. Lingual orthodontic appliances are preferred over labial by patients because of its invisibility. The aim of this research is to compare the Von Mises stress distribution and displacement of palatal implants in the lingual orthodontic system among four different combinations of palatal implant and lever arm. Materials and Method: Four Finite element models were constructed for the bilaterally extracted first premolar maxillary arch. In all these models 0.018” slot lingual brackets were placed at the center of the clinical crown. A similar retraction force (150gm) was applied with the help of NiTi closed coil spring for all the models but the length of the lever arm vary as well as the palatal implant position also varies in these models. Finite element analysis was then performed to compare the Von Mises stress distribution, and displacement of the palatal implant using ANSYS 12.1 software. Result: In this study, displacement was the same (0.0005 mm) for all four models. Highest amount von mises stress was observed in Model 3 (3.4798 MPa) as a comparison to Model 1 (2.5442 MPa), Model 2 (2.5018 MPa), and Model 4 (3.3854 MPa). The stress value for the palatal implant was within the acceptable fatigue limit of the titanium of 193 MPa therefore all four models combination was safe for the clinical application. Conclusion: Double palatal implant systems were more effective in comparison to the single palatal implant system in lingual orthodontics. In this study, we found that the displacement of the palatal implants was not affected by the length of the lever-arm and the amount of stress was decreased when we increase the length of the lever-arm.